Efforts to Improve the Quality of Islamic Education Institutions in the Millennium Era: Case Study in MI Darwata Mujur Lor Kroya Cilacap - Aziz, Mursida (International Conference of Moslem Society, 2019)
In the millennium era the competition between educational institutions is getting tougher. If an institution does not innovate in improving an educational institution, it will lag behind other educational institutions. After the researchers observed the MI Darwata Mujur Lor Educational Institution, the researchers found a lack of proportional improvement in the ability of teachers and a lack of networks that were integrated with the community. The purpose of this study was to determine the efforts made by MI Darwata Mujur Lor in improving the quality of its institutions. The type of the research is descriptive research. Descrpitive research is done by collecting data as much as possible which is supporting factors that influence it then explained according to the data found. Data collection techniques in this study were interviews, observation, surveys and documentation. The analysis technique of this study using taxonomic analysis is the analysis of the chosen domain which is further elaborated to find out the internal structure using focused observation. The results showed that efforts to improve the quality of educational institutions in Darwata Mujur Lor in the aspects of teacher professionalism were carried out by improving the profession individually, and increasing teachers through professional organizational channels, and network aspects carried out by conducting workshops / training internally, collaborating with school committee, collaborate with the community, and collaborate with local agencies and non-governmental institutions.